Hypertension and diabetes screening uptake in adults aged 40–70 in Indonesia: a knowledge, attitudes, and practices study - Maja E. Marcus; Anna Reuter; Lisa Rogge; Farah Diba; Marthoenis; Sebastian Vollmer (BMC Global and Public Health)
Abstract Background Diabetes and hypertension are major global health crises, yet Indonesia is lagging behind in achieving care outcomes compared to other middle-income countries. We examined barriers to screening uptake, a key care entry point, in 40–70-year-old adults in Aceh, Indonesia. Methods We assessed individual-level data on diabetes and hypertension screenings in Banda Aceh and Aceh Besar in 2019. Using two-stage random sampling, we collected survey data on 2080 adults that are indicated for, but had not undergone diabetes screening as per World Health Organization’s Package of Essential Noncommunicable Disease Intervention guidelines. Using this, we adjusted the data for complex survey design to describe (1) the share of respondents with screening indication and presence of risk factors; (2) disease-related knowledge, attitude, and practices, as well as (3) estimate associations of screening with socioeconomic characteristics, knowledge, and attitudes using multivariable linear and logistic regression. Results We found that while respondents were aware of diabetes and hypertension, a majority lacked knowledge about leading risk factors, the conditions’ potentially asymptomatic nature, and screening needs. About 41% of respondents never had any blood pressure or glucose check, the primary reason reported being not feeling ill. Blood glucose checks were rarely conducted. We found rural location and lower education to be associated with lower disease-related knowledge, and lower wealth with lower knowledge and screening uptake. Conclusions Barriers to screening uptake in Aceh, Indonesia, include misconceptions around hypertension and diabetes, provider-specific challenges especially around the provision of glucose testing, and socioeconomic gradients.